Electric field-directed growth and photoelectrochemical properties of cross-linked Au–ZnO hetero-nanowire arrays. Issue 11 (23rd December 2014) - Wang, Teng; Jin, Bingjun; Jiao, Zhengbo; Lu, Gongxuan; Ye, Jinhua; Bi, Yingpu
Abstract : Herein, we demonstrate a simple and effective strategy for vertically growing Au nanowires over ZnO nanowire arrays to construct a cross-linked hierarchical architecture, which exhibit excellent photoelectrochemical performances under visible light irradiation. Abstract : We demonstrate a simple and effective strategy for vertically growing Au nanowires over ZnO nanowire arrays to construct a cross-linked hierarchical architecture under the synergistic effects of the electric field direction and photoreduction, which exhibit excellent photoelectrochemical performances under visible light irradiation.